Precision Glycoproteomics Reveals Distinctive N-Glycosylation in Human Spermatozoa - Xin, Miaomiao; You, Shanshan; Xu, Yintai; Shi, Wenhao; Zhu, Bojing; Shen, Jiechen; Wu, Jingyu; Li, Cheng; Chen, Zexuan; Su, Yuanjie; Shi, Juanzi; Sun, Shisheng (Molecular and cellular proteomics, 2022)
Spermatozoon represents a very special cell type in human body, and glycosylation plays essential roles in its whole life including spermatogenesis, maturation, capacitation, sperm-egg recognition, and fertilization. In this study, by mapping the most comprehensive N-glycoproteome of human spermatozoa using our recently developed site-specific glycoproteomic approaches, we show that spermatozoa contain a number of distinctive glycoproteins, which are mainly involved in spermatogenesis, acrosome reaction and sperm:oocyte membrane binding, and fertilization. Heavy fucosylation is observed on 14 glycoproteins mostly located at extracellular and cell surface regions in spermatozoa but not in other tissues. Sialylation and Lewis epitopes are enriched in the biological process of immune response in spermatozoa, while bisected core structures and LacdiNAc structures are highly expressed in acrosome. These data deepen our knowledge about glycosylation in spermatozoa and lay the foundation for functional study of glycosylation and glycan structures in male infertility.
Keywords: Glycoproteins; spermie; glykoproteiny; Acrosome; Spermatozoa; Male; glykosylace; lidé; kapacitace spermií; akrozom; mužské pohlaví; Glycosylation; Acrosome Reaction; Sperm Capacitation; Humans; akrozomální reakce